Development Of Web Application Based On Crowdsourcing For Car Rental Managementby Using Scrum Methodology (rental Side) - Faqih Putra Kusumawijaya; Soni Fajar Surya Darmawan; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract— Car rental business in Indonesia was highly developed, as seen from the number of rental cars more and more especially in big cities in Indonesia, one of them are the rental in SMEs scale. On the other hand, technological development has been very fast, especially internet technology. With its consistent growth, car rental business should utilize the technology to improve business development. With the use of technology, the rental business will be expanding and getting larger and increasingly professional rental management. One that can develop is to apply the concept of crowdsourcing. With crowdsourcing, rental owner will be able to easily manage the marketing of rental and can easily increase the number of cars without having to own a car. Because the owner of the car that will participate rent the car, can directly contact the relevant rental. Application development is done with the scrum method. This method was chosen with the expectation generated application can be in accordance with the wishes of the user. This application will be equipped with SMS Gateway technology in terms of the notification. Also the development of this application using Laravel Framework whose capabilities is proven. Keyword—Car Rental, business, technology, scrum, framework, laravel, crowdsourcing, SMS Gateway